Playing dead - Rothschild, Peggy (A Molly Madison mystery, 2023)
"Molly Madison is back to solve another doggone difficult murder in her California community. Molly Madison has barely had a moment to catch her breath after moving to the sleepy beach town she now calls home. But as a former PI, she can't help but notice the odd chemistry between members of Playtime Academy on the first day she and her loyal Saint Bernadoodle, Noodle, and golden retriever, Harlow, visit. When a trainer's body is found on-site, Molly knows it's her duty to put her ex-police skills to use. She can't say no to temporarily taking in the deceased woman's dog, either-not with those puppy dog eyes. Relationships at the training facility are not as clean as the prize-winning agility runs, making it difficult for Molly to get a leash on potential suspects. And her personal life is just as messy-her boyfriend is hiding something, her agoraphobic neighbor needs help, and her number of four-legged friends keep growing as she agrees to dogsit a wriggly local French bulldog. When Molly's friend is arrested for the murder, she's not sure who to believe anymore. Is the case as simple as the local cops make it seem, or is something more devious afoot?"--